RESISTENSI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERINTEGRASI PADA KINERJA GURU DI KELAS - Edy Suprayetno; Jusrin Efendi Pohan (Jurnal Education and Development, 2022)
The purpose of this study was to describe the correlation of integrated principals' transformational leadership on the performance of teachers at SMA N 1 Medan City. The problems found in the field are the low ability of school principals in motivating teachers to work and innovate. This type of research is quantitative research using a survey method involving 80 teachers as respondents. Data collection techniques were carried out by distributing questionnaires to teachers, structured interviews, and in-depth observations. Data were analyzed by t test and f test. Data analysis was carried out by simple regression to determine the relationship of each variable X to Y, then using multiple regression formulas to determine the contribution of X1 and X2 together to variable Y. Before testing the hypothesis, the classical assumption was first tested, which consisted of from the normality assumption test, heteroscedasticity test, serial correlation test and multicollinearity test, and the second is regression analysis test. The findings of this study are that the principal's transformational leadership can improve the performance of teachers to be creative and innovate.